FACTORS INFLUENCING THE MANAGEMENT OF VILLAGE FUND ALLOCATION (ADD) IN MUARA BADAK DISTRICT, KUTAI KARTANEGARA REGENCY - Hana, Nur; Hayat, Atma; Rasida, Rasida (JEA17: Jurnal Ekonomi Akuntansi, 2024)
This study aims to test and analyze the Factors that Influence the Management of Village Fund Allocation (ADD) in Muara Badak District. The factors in this study are the role of village officials, internal control systems, transparency, competence, compliance with regulations. The problem of Village Fund Allocation distributed by the Central Government to very large villages really needs good management, to maintain public trust in the Village Government. This study was conducted in all villages in Muara Badak District, Kutai Kartanegara Regency. The population in this study was all village officials in Muara Badak District, Kutai Kartanegara Regency. Data were taken from the questionnaires that were distributed, and produced 94 respondents from 101 village officials. The data analysis method used multiple linear regression. The results of this study indicate that the variables of the role of village officials and the internal control system have a positive effect on the management of village fund allocation (ADD). This shows that the higher the role of village officials and the internal control system of village officials, the better the management of village fund allocation (ADD) produced, while the variables of transparency, competence, and compliance with regulations do not affect the management of village fund allocation (ADD).